Pengaruh Metode Tartil dan Pembinaan Guru terhadap Peningkatan Kemampuan Baca Tulis Al-Qur'an Santri Taman Pendidikan Al-Qur’an - Azizah, Aulia; Budiwan, Jauhan; Samsudin, Samsudin (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The study aims to determine the following: (1) the effect of the At-Tartil method on students' ability to read and write the Al-Qur'an, (2) the effect of teacher coaching on students' ability to read and write the Al-Qur'an, and (3) the simultaneous effect of the At-Tartil method and teacher coaching on students' ability to read and write the Al-Qur'an at TPA Al-Musyarrof in Bantengan Village, Madiun Regency. The research method is a descriptive quantitative Correlational Survey design. The study population consisted of 280 active students and 15 teachers. A total of 55 respondents were sampled (40 students and 15 teachers). Data were collected through questionnaires, observations, and documentation. Data were analyzed in several stages, including a descriptive statistics test, a normality test, a linearity test, a one-sample t-test, and a multiple linear regression test. The results showed the following: (1) The At-Tartil Method significantly improves the ability to read and write the Quran, with an average score of 87.98 and a significance level of 0.000. (2) Teacher coaching also significantly improves the ability to read and write the Quran, with an average score of 87.07 and a significance level of 0.000. (3) The partial regression coefficient test results show that neither the At-Tartil Method (sig. 0.489) nor teacher coaching (sig. 0.413) have a significant individual effect, as both are greater than 0.05. The collinearity statistics test results show tolerance and VIF values of 1.000, indicating an absence of multicollinearity symptoms between the independent variables. Together, the method and coaching have not been able to explain the variation in students' abilities as a whole. A more integrated approach is needed that considers factors such as students' cognitive readiness and the support of their learning environment.